(untitled) (Research, Society and Development, 2024)
The central objective of this article is to understand the relationship between aesthetics, consumption and food waste, notably fruits, vegetables and greens (FVs) and how this determines both consumption patterns and waste of these foods. And also, as a secondary objective, to point out some ways to reevaluate current consumption patterns and establish new ones, aiming to minimize the waste of FVs. Through a narrative literature review covering the areas of philosophy, arts, consumer sciences (marketing, consumer behavior, etc.), food sciences and history, primarily, and sociology, economics and psychology, secondary, the article uses the aesthetic categories of beauty and ugly, perfect and imperfect, as well as the concept of aesthetic judgment to complete a brief historical journey of aesthetics, and not only understand consumer preferences and choices for FVs considered “beautiful” and aesthetically perfect, as well as the consequences of such preferences and choices on social well-being and the environment. Using the concepts of “everyday aesthetics” and “imperfectionist aesthetics”, as well as “food artevism” and “gastropolitics”, the work explores the potential of art and gastronomy to, through aesthetic experience, highlight ethical issues related to food consumption and waste, with the aim of contributing to rethinking rigid and stereotypical concepts and standards.